Digital Literacy and Data Security Training for Digital Era Village Cooperative Management - Abdul Wahid; Syarif Aminul Khoiri (TGO Journal of Community Development, 2025)
The Merah Putih Village Cooperative is a village cooperative that has a strategic role in strengthening the people's economy, especially through savings and loan services and trading agricultural products. However, in the digital era, cooperatives still face challenges in the form of low digital literacy of administrators and weak management of member data security. Administrative processes that are still manual and have minimal understanding of cybersecurity risks have the potential to hinder the operational effectiveness and sustainability of cooperatives. This community service activity aims to increase digital literacy and data security awareness for the management of the Merah Putih Village Cooperative through a participatory and collaborative approach. Implementation methods include problem identification, programme dissemination, digital literacy and data security training, application of cloud-based technologies, and post-training mentoring and evaluation. Training includes the use of digital productivity applications, cloud-based document management, as well as the implementation of data security practices such as the use of strong passwords, two-factor authentication and data backup. The results of the activity show a significant increase in the digital competence of the management, the efficiency of cooperative administration, as well as increasing awareness of the importance of member data protection. This activity is the first step in the digital transformation of village cooperatives towards more effective, safe, transparent and sustainable governance, while strengthening synergies between universities, village governments and the community.